Implementation of the Water Framework Directive in an outermost EU region : the case of Azores archipelago - Cruz, J. Virgílio (2012)
The Azores Water Plan (AWP) came to force in year 2003 in order to provide a coherent set of measures to protect and enhance water resources in the archipelago. The AWP was developed according to EU Water Framework Directive (WFD) and a close relationship can be found between goals on both documents. The evaluation of results associated to AWP implementation, made possible through a consultation procedure described in the present paper, provides an indirect assessment of the implementation of the WFD in an EU outermost region such as the Azores. The analysis suggests that major constrains to the full implementation of the AWP and WFD are associated with administrative arrangements, reflected in a lack of coordination, as well as adequate funding and cost recovery and strategies for public participation and information provision. Instead, water quality monitoring is already fully operational showing a strong relationship between science and water policy.